The Use of Word Card Media for Letter Recognition in Early Students - Robiatul, Liza; Basri, Muhammad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research aims to determine how word card media affects children's letter recognition. Classroom teachers were questioned during data collection, along with other teachers, and learning activities were checked. This study used a qualitative method with a case study approach at PAUD al-Khoiriyah Tanjung Botung, Simangambat, Padang Lawas Utara, Sumatra Utara. This study uses a qualitative method with a case study approach. The research data is in the form of letter recognition activities using word cards as media. Researchers obtained data from school principals, class teachers, accompanying teachers, students, and several parents of students. Collecting data through observation, interviews, and documentation While data analysis is done by data reduction, data presentation, conclusion, and verification, The results of the study show that letter recognition using word card media can be passed by 1. The word cards are prepared by the teacher and distributed to students. 2. The teacher arranges the word cards that students will arrange by compiling the alphabet cards he gives according to the words proposed by the teacher. 3 The young person reads each letter and word aloud before the other groups.